1996
DOI: 10.1111/j.1467-9280.1996.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Happiness Is a Stochastic Phenomenon

Abstract: Happiness, or sllbjecti~'e Il'ell-beillg, Il'as measllred on a birth-record-based sample of serernl thousand middleaged twins IIsing the Well-Being (WB) scale of the MlIltidimensional Personality Questionnaire. Neither socioeconOlllic staillS, edllcational attainlllell1, family income, marital stallls, nor an indicant of religious cOllllllitmell1 could account for more than abollt 3% ofthe variance in WB. From 44% to 52% ofthe variance ill WB, hOll'ever, is associated Il'ith genetic variation. Based on the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
852
8
47

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,299 publications
(958 citation statements)
references
References 8 publications
51
852
8
47
Order By: Relevance
“…This set point describes a relatively stable intensity level and contains a strong genetic component (e.g., [33]). At times, the state aspect of SWB varies strongly around this individual set point as an outcome of interactions between situational stimuli (e.g., exercise) and personality (e.g., extraversion).…”
Section: Dynamic Aspects Of Swbmentioning
confidence: 99%
“…This set point describes a relatively stable intensity level and contains a strong genetic component (e.g., [33]). At times, the state aspect of SWB varies strongly around this individual set point as an outcome of interactions between situational stimuli (e.g., exercise) and personality (e.g., extraversion).…”
Section: Dynamic Aspects Of Swbmentioning
confidence: 99%
“…In one of the strongest statements against the possibility for change, Lykken and Tellegen (1996) suggested that "trying to be happier [may be] as futile as trying to be taller" (p. 189). These authors based this statement on evidence from behavioral genetic studies.…”
mentioning
confidence: 99%
“…Em relação aos fatores que influenciam o BES, convém lembrar que este construto sofre influência tanto cultural (experiências compartilhadas que formam a base de uma maneira similar de ver o mundo) como da hereditariedade (Albuquerque & Tróccoli, 2004;Lykken & Tellegen, 1996). O sentido das experiências dos indivíduos é construído socialmente por meio de crenças, pressuposições e expectativas sobre o mundo ligadas também à transmissão que ocorre no âmbito da família.…”
Section: Bem-estar Subjetivo: O Estudo Científico Da Felicidadeunclassified